PROGRAM BANTUAN PANGAN NON TUNAI (BPNT): STUDI EVALUASI DI KECAMATAN MAGERSARI KOTA MOJOKERTO - Gratia Uli Septriana Munthe; Singgih Manggalou (Journal Publicuho, 2025)
This study aims to evaluate the implementation of the Non-Cash Food Assistance Program (BPNT) in Magersari District, Mojokerto City, using the Bridgman and Davis evaluation model, which covers input, process, outputs, and outcomes. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results of the study indicate that from the input aspect, the allocated budget is not fully sufficient for household needs, and the availability of human resources in the distribution process is still limited. From the process aspect, the implementation mechanism is systematic, but the distribution does not run every month. From the output aspect, the amount of assistance received is in accordance with provisions, and from the outcome aspect, there are positive impacts in the form of reduced household expenses and profits for e-warongs, as well as negative impacts in the form of limited commodity quantities. Thus, the BPNT program has been running quite effectively, but still requires improvements in terms of increasing the budget, adding human resources, and strengthening coordination between stakeholders.